El Niño-Southern Oscillation and frost occurrence in the Guarapuava-PR region (Research, Society and Development, 2020)
The association of the characteristics of the El Niño–Southern Oscillation (ENSO) phases with local conditions, are important tools to be used in the generation of information inherent to the risks of frosts. Despite its great impact in the southern region of Brazil and in other parts of the world, frosts are events that are difficult to predict because they result from the interaction of different climatic conditions. This study aimed to analyze the occurrence of frost during the years of El Niño, La Niña and neutrality in the region of Guarapuava-PR. A historical database of 43-year-old climate variables (1976 to 2018) was subsequently crossed with ENSO data obtained from the National Oceanic and Atmospheric Administration (NOAA). It was found that periods of climatic neutrality are predominant in relation to the extreme phases of ENSO and have a higher frequency of frost events. In this condition, the frequency of frosts is 67% in relation to 20% and 13% in La Niña and El Niño, respectively.